Perspectives on family caregiving of people aging with intellectual disability affected by dementia: Commentary from the International Summit on Intellectual Disability and Dementia - Jokinen, Nancy; Gomiero, Tiziano; Watchman, Karen; Janicki, Matthew P.; Hogan, Mary; Larsen, Frode; Beránková, Anna; Heloísa Santos, Flávia; Service, Kathy; Crowe, Jim (Taylor & Francis, 2018)
This article, an output of the 2016 International Summit on Intellectual Disability and Dementia, examines familial caregiving situations within the context of a support-staging model for adults with intellectual disability (ID) affected by dementia. Seven narratives offer context to this support-staging model to interpret situations experienced by caregivers. The multidimensional model has two fundamental aspects: identifying the role and nature of caregiving as either primary (direct) or secondary (supportive); and defining how caregiving is influenced by stage of dementia. We propose staging can affect caregiving via different expressions: (1) the “diagnostic phase,” (2) the “explorative phase,” (3) the “adaptive phase,” and (4) the “closure phase.” The international narratives illustrate direct and indirect caregiving with commonality being extent of caregiver involvement and attention to the needs of an adult with ID. We conclude that the model is the first to empirically formalize the variability of caregiving within families of people with ID that is distinct from other caregiving groups, and that many of these caregivers have idiosyncratic needs. A support-staging model that recognizes the changing roles and demands of carers of people with ID and dementia can be useful in constructing research, defining family-based support services, and setting public policy.
Keywords: caregivers; caregiving; Dementia; Down syndrome; intellectual disability; narratives